Where do we go from here? Exploring the future of mixed families between Italy and South Asia. (March 2021) - Bonfanti, Sara
Family labor migration from South Asia to Europe is often framed as proceeding in a predictable pattern of "male first-time migrant, ethnic marriage and spouse reunion." Migration to Northern Italy is no exception. Primary data from recent ethnographic fieldwork reveal a slow rise in mixed South Asian–Italian couples, which might bring into question the quandaries they face in raising children. This article considers the daily struggles in conjugal and parental relations in mixed-culture households formed by spouses, one of whom is from a South Asian background, and the other is an Italian "native." Applying intersectional analysis to the life stories and aspirations of such cross-cultural new generations allows for revisiting the commonplace view of South Asia–Europe intimate links.